Efficacy and Safety of a Polysaccharide-Based Natural Substance Complex in the Treatment of Obesity and Other Metabolic Syndrome Components: A Systematic Review - Guarino, Giuseppina; Strollo, Felice; Malfertheiner, Peter; Della Corte, Teresa; Stagi, Stefano; Masarone, Mario; Gentile, Sandro (Frontiers in Drug Safety and Regulation, 2022)
Abstract Introduction: Metabolic syndrome (MetS) is increasingly common in adults as well as in children and adolescents. However, preventing and treating MetS is one of the most pressing challenges for public health services worldwide. At present, the only approved treatments for MetS are dietary changes and physical activity, which are associated with a high rate of non-compliance. On the contrary, no drugs are licensed to treat metabolic syndrome although a number of drugs are used to treat individual metabolic abnormalities, which increases the risk of adverse events, particularly in children. Policaptil Gel Retard®(PGR), an oral macromolecule complex based on polysaccharides, has been demonstrated to significantly reduce body weight, peak blood glucose (BG) levels, insulin levels and lipid levels, providing an interesting non-pharmacological therapeutic option for MetS-associated metabolic abnormalities, especially in younger patients. Aims: To review available studies on the use of PGR in children, adolescents or adults with obesity or metabolic syndrome. Methods: A systematic search of electronic databases for PGR and MetS. A total of six studies were identified and included. Results: Across four randomised clinical studies and one retrospective clinical study including a total of 359 obese children and adolescents with or without MetS and 157 overweight/obese adults with or without MetS and/or T2DM, a single dose of PGR resulted in a reduction in appetite and postprandial triglyceride levels in younger patients and in peak postprandial BG levels in adults. Decreased lipid levels were observed in adults following a normo-caloric diet who received PGR for 30 days. As a long-term treatment, in combination with a low-glycaemic index diet with or without metformin, PGR resulted in reduced body mass index and waist circumference, improved insulin sensitivity with reduction of glucose-metabolism abnormalities, increased insulin reserve and, finally, an improved circulating lipid profile, regardless of age. No safety issues were reported. Conclusions: Policaptil Gel Retard® is an effective and safe non-pharmacological approach to improving the treatment of MetS-associated cardiovascular risk factors in children, adolescents and adults.